Diversity, inclusion, and decolonization : practical tools for improving teaching, research, and scholarship - Day, Abby, 1956-; Lee, Lois (Research associate); Thomas, Dave S. P.; Spickard, James V. (Bristol University Press, 2022)
Despite progress, the Western higher education system is still largely dominated by scholars from the privileged classes of the Global North. This book presents examples of efforts to diversify points of view, include previously excluded people, and decolonize curricula. What has worked? What hasn't? What further visions do we need? How can we bring about a more democratic and just academic life for all? Written by scholars from different disciplines, countries, and backgrounds, this book offers an internationally relevant, practical guide to 'doing diversity' in the social sciences and humanities and decolonising higher education as a whole.